A diverse Late Cretaceous vertebrate tracksite from the Winton Formation of Queensland, Australia - Poropat, Stephen F.; White, Matt A.; Ziegler, Tim; Pentland, Adele H.; Rigby, Samantha L.; Duncan, Ruairidh J.; Sloan, Trish; Elliott, David A. (PeerJ, 2021)
The Upper Cretaceous ‘upper’ Winton Formation of Queensland, Australia is world famous for hosting Dinosaur Stampede National Monument at Lark Quarry Conservation Park, a somewhat controversial tracksite that preserves thousands of tridactyl dinosaur tracks attributed to ornithopods and theropods. Herein, we describe the Snake Creek Tracksite, a new vertebrate ichnoassemblage from the ‘upper’ Winton Formation, originally situated on Karoola Station but now relocated to the Australian Age of Dinosaurs Museum of Natural History. This site preserves the first sauropod tracks reported from eastern Australia, a small number of theropod and ornithopod tracks, the first fossilised crocodyliform and ?turtle tracks reported from Australia, and possible lungfish and actinopterygian feeding traces. The sauropod trackways are wide-gauge, with manus tracks bearing an ungual impression on digit I, and anteriorly tapered pes tracks with straight or concave forward posterior margins. These tracks support the hypothesis that at least one sauropod taxon from the ‘upper’ Winton Formation retained a pollex claw (previously hypothesised for Diamantinasaurus matildae based on body fossils). Many of the crocodyliform trackways indicate underwater walking. The Snake Creek Tracksite reconciles the sauropod-, crocodyliform-, turtle-, and lungfish-dominated body fossil record of the ‘upper’ Winton Formation with its heretofore ornithopod- and theropod-dominated ichnofossil record.
Keywords: Dinosauria; Sauropoda; Theropoda; Ornithopoda; Crocodyliformes; Testudines; Dipnoi; Actinopterygii; Swim tracks; Ichnology